ECOLOGICAL RESTORATION OF RANCHO PIRAJUSSARA, DESCALVADO, SP - Scanavaca JÃºnior, Laerte; Adorno, Maria de Fatima Christe (REVISTA DE AGRICULTURA, 2021)
Riparian area is the last and the best protection that a river can have because it prevents the arrival of physical, chemical, and biological pollutants in the body of water. After a fire in a riparian forest that is in a transition between the seasonal semi-deciduous forest and the savanna, its restoration processes began. The area was taken over by 3 m high colonial grass. Some trees resisted the fire and served as perches for birds. We planted 48 species of 28 families with three basic objectives, fruits for human consumption, shelter and food for fauna and other uses (medicinal and lumber). The cost of implementation was US $ 6,104.21 per hectare. The restoration was good due to the low percentage of failure (33.27%), despite the great drought that occurred at the time of implantation. The average height of the trees was over 2 m at four years.